Artemisinin Attenuated Atherosclerosis in High-Fat Diet–Fed ApoE−/− Mice by Promoting Macrophage Autophagy Through the AMPK/mTOR/ULK1 Pathway. Issue 4 (April 2020) - Cao, Qian; Du, Hongjiao; Fu, Xi; Duan, Na; Liu, Changhe; Li, Xiaodong
Abstract : Abstract: Artemisinin is an endoperoxide sesquiterpene lactone from Artemisia annua L with multiple beneficial effects, including anti-inflammation, antioxidant, and vascular protection. Recent studies have found that inflammation along with autophagy deficiency in macrophages is the possible reason for foam cell accumulation in the intima, which leads to atherosclerotic plaque formation. The primary aims of this study were to explore the inhibiting effect of artemisinin on atherosclerosis in high-fat diet–fed ApoE −/− mice and investigate the probable mechanism. Artemisinin (50 and 100 mg/kg, intragastric administration) treatment effectively inhibited foamy macrophage transformation and decreased atherosclerotic plaque formation in atherosclerotic mice. Moreover, artemisinin promoted AMP-activated protein kinase (AMPK) activation, inhibited mammalian target of rapamycin (mTOR) and uncoordinated-51-like kinase 1 (ULK1) phosphorylation, and increased LC-3II accumulation and P62 degradation, thereby enhancing macrophage autophagy. Besides, the inhibiting effect of artemisinin on mTOR and ULK1 phosphorylation could be abrogated by AMPK knockdown, suggesting AMPK was the essential target of artemisinin on promoting macrophage autophagy. Our study indicated that artemisinin alleviated atherosclerotic lesions by accelerating macrophage autophagy through the AMPK/mTOR/ULK1 pathway. Abstract : Supplemental Digital Content is Available in the Text.